4AA Model as a Task-based Research Writing Framework for Undergraduates - Camara, Jun S; Tubera, Rhegina F (ASEAN Multidisciplinary Research Journal, 2022)
Writing as an intellectual enterprise does not have to be performed individually; it is supposed to be a collaborative activity. Adopting the principles of the self-efficacy theory, community of inquiry framework, and collaborative learning framework, this study proposed a task-based approach known as 4AA Model for writing the results and discussion section of a technical paper written in the IMRAD Format. Using an exploratory mixed method design (i.e. developmental and survey) during the first semester of school year 2021-2022, the participants as end-users of the model (n=80, HEI faculty and students) claimed based on the survey results that the model could be used in the teaching of writing in college. Further, majority rated the model as practical and its attributes are doable. When asked their ability to perform the indicators covered in the Model, the participants registered means of ‘moderate ability’, with the HEI faculty reporting higher weighted means. On the 4AA Model structure, the competencies for the 3rd-author are rated the most difficulty while those of the 1st-author are rated the easiest. Moderate abilities of the participants were perceived for the 2nd-author type. The researchers conclude that the 4AA Model could be used in the teaching of research subjects in college, and a training manual based on the perceived abilities of the participants is recommended.